2018
DOI: 10.2147/lra.s185554
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia to ameliorate postoperative analgesia outcomes in pediatric surgical patients: an updated systematic review of randomized controlled trials

Abstract: Regional anesthesia is becoming increasingly popular among anesthesiologists in the management of postoperative analgesia following pediatric surgery. The main objective of this review was to systematically evaluate the last 5 years of randomized controlled trials on the role of regional anesthesia techniques in alleviating postoperative pain associated with various pediatric surgical procedures. Forty studies on 2,408 pediatric patients were evaluated. The majority of the articles published from 2013 to 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 211 publications
1
28
0
Order By: Relevance
“…Until few years ago, caudal block, TAP block, and ilioinguinal/iliohypogastric block were the most often used analgesic techniques for low abdominal surgery (inguinal hernia repair, and orchidopexy) in pediatric patients. Caudal block provides postoperative analgesia as good as TAP block, and both of them provide better analgesia than ilioinguinal/iliohypogastric block according to prospective randomized single-blinded study by Sahin et al [22] Kendall et al reached the same conclusion in their systematic review of 40 randomized controlled trials in 2018 [21]. Therefore, recently published data suggest that QLB provides significantly more effective, and longer lasting analgesia than caudal block in pediatric patients undergoing inguinal hernia repair, orchidopexy, and ureteral reimplantation [10,12,16].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Until few years ago, caudal block, TAP block, and ilioinguinal/iliohypogastric block were the most often used analgesic techniques for low abdominal surgery (inguinal hernia repair, and orchidopexy) in pediatric patients. Caudal block provides postoperative analgesia as good as TAP block, and both of them provide better analgesia than ilioinguinal/iliohypogastric block according to prospective randomized single-blinded study by Sahin et al [22] Kendall et al reached the same conclusion in their systematic review of 40 randomized controlled trials in 2018 [21]. Therefore, recently published data suggest that QLB provides significantly more effective, and longer lasting analgesia than caudal block in pediatric patients undergoing inguinal hernia repair, orchidopexy, and ureteral reimplantation [10,12,16].…”
Section: Discussionmentioning
confidence: 89%
“…Regional analgesia techniques reduce opioid consumption during general anesthesia perioperatively, and provide better postoperative pain control compared to pain control provided by either general anesthesia alone or general anesthesia plus local anesthetic wound infiltration [13,14,21]. Until few years ago, caudal block, TAP block, and ilioinguinal/iliohypogastric block were the most often used analgesic techniques for low abdominal surgery (inguinal hernia repair, and orchidopexy) in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric regional anesthesia is being used increasingly as a part of the anesthetic approach combined with general anesthesia to decrease the intraoperative anesthetic requirement with rapid recovery; at the same time, provides postoperative analgesia [17].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of randomized controlled trials demonstrated that regional anesthesia decreased opioid consumption and minimized postoperative pain with no significant complications attributed to its use. 13 Additional studies are needed to better delineate specific surgical procedures and subpopulations of pediatric patients in which regional anesthesia may provide the most benefit. Abbreviations: IV, intravenous; LA, local anesthetic; PCA, patient-controlled analgesia; PO, oral; PR, rectal.…”
Section: Regional Anesthesiamentioning
confidence: 99%